Risk Factors of Very Severe RSV Infections in a Multicenter Cohort of Very Preterm and Extreme Preterm Babies Receiving or Not Palivizumab - Mulot, Gwenaelle; Benchaib, Mehdi; Plaisant, Frank; Ploin, Dominique; Gillet, Yves; Javouhey, Etienne; Claris, Olivier; Picaud, Jean-Charles; Casalegno, Jean-Sebastien; Butin, Marine (Frontiers in Pediatrics, 2022)
Introduction Preterm infants are at risk of lower respiratory tract infections(LRTI), including Respiratory Syncytial Virus (RSV) associated bronchiolitis, for which palivizumab prophylaxis can be proposed. Our aim was to determine risk factors of very severe RSVdisease in children born before 34 weeks of gestation. Methods Among 2101 infants born before 34 weeks of gestation in 3 maternity wards between 2012 and 2017, the laboratory confirmed RSV-infected patients requiring hospitalization before 12 months of corrected age were retrospectively included. We collected data about the neonatal period, the palivizumab prophylaxis and the hospitalization for a RSV-related LRTI. LRTI was considered as very severe(VS-LRTI) when patients required invasive or non-invasive positive pressure ventilation. Results Among 86 included patients, 31 met the criteria of VS-LRTI. The VS-LRTI patients had a higher birth gestational age and weight but less heart disease and bronchopulmonary dysplasia. They received palivizumab prophylaxis less frequently than the other patients but the difference was not significant. At the onset of infection,VS-LRTI patients had a younger corrected age for prematurity and presented more frequently with apnea, bradycardia, life-threatening event, hemodynamic failure, hypercapnia. Using logistic regression, the main factor associated with VS-LRTI was a younger corrected age for prematurity at the onset of infection(Odd ratio for each month of corrected age = 0.77[0.62; 0.93], p=0.012). Conclusion Infants at the highest risk of VS-LRTI were infants with a younger corrected age for prematurity. Therefore, a better targeting of infants requiring palivizumab prophylaxis and early interventions at hospital discharge could limit VS-LRTI in these infants.